2011
DOI: 10.1021/np100784t
|View full text |Cite
|
Sign up to set email alerts
|

Cycloartane Triterpenes Isolated from Combretum quadrangulare in a Screening Program for Death-Receptor Expression Enhancing Activity

Abstract: In our screening program for natural products that increase DR5 (death-receptor 5) expression, nine new cycloartane triterpenes, combretanones A-G (1-7), combretic acid A (8), and combretic acid B (9), were isolated from a MeOH extract of Combretum quadrangulare leaves. The known oleanane triterpenes (10, 11) and six known flavonols (12-17) were also isolated. The structures of 1-9 were elucidated by spectroscopic studies. Compounds 7, 9, 12, 16, and 17 enhanced DR5 expression, and 16 showed TRAIL-resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
1
29
0
3
Order By: Relevance
“…111 11 -acetoxy-20,24-epoxy-25-hydroxy-dammar-3-one C. nigricans [43] 112 20,24-epoxy-11 ,25-dihydroxy-dammar-3-one C. nigricans [43] 113 20,24-epoxy-12 ,25-dihydroxy-dammar-3-one C. nigricans [43] 114 arcapitin A C. nigricans [43] 115 ursolic acid C. zeyheri C. quadrangulare C. vendae C. yannanense [44,45,46,54] 116 corosolic acid C. vendee [46] 117 oleanolic acid C. zeyheri [46] 118 maslinic acid…”
Section: Triterpenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…111 11 -acetoxy-20,24-epoxy-25-hydroxy-dammar-3-one C. nigricans [43] 112 20,24-epoxy-11 ,25-dihydroxy-dammar-3-one C. nigricans [43] 113 20,24-epoxy-12 ,25-dihydroxy-dammar-3-one C. nigricans [43] 114 arcapitin A C. nigricans [43] 115 ursolic acid C. zeyheri C. quadrangulare C. vendae C. yannanense [44,45,46,54] 116 corosolic acid C. vendee [46] 117 oleanolic acid C. zeyheri [46] 118 maslinic acid…”
Section: Triterpenoidsmentioning
confidence: 99%
“…2 ,3 -dihydroxyurs-12-èn-28-oic acid C. zeyheri [44] 120 6 -hydroxymaslinic acid C. zeyheri [44] 121 terminolic acid C. zeyheri [44] 122 methylsumaresinolate C. zeyheri [44] 123 combretanone A C. quadrangulare [45] 124 combretanone B C. quadrangulare [45] 125 combretanone C C. quadrangulare [45] 126 combretanone D C. quadrangulare [45] ( [34] 162 kinkeloid A2 C. micranthum [34] 163 kinkeloid B1 C. micranthum [34] 164 kinkeloid B2 C. micranthum [34] 165 kinkeloid C1 C. micranthum [34] 166 kinkeloid C2 C. micranthum [34] 167 kinkeloid D1 C. micranthum [34] 168 kinkeloid D2 C. micranthum [34] 169 apigenin C. erythrophyllum [50] 170 genkwanin C. erythrophyllum [50] 171 5-hydroxy-7,4 -dimethoxyflavone C. erythrophyllum [50] 172 Rhamnocitrin C. erythrophyllum C. apiculatum [50,51] 173 kaempferol C. erythrophyllum C .apiculatum [50,51] 174 quercetin-5,3 -dimethylether C. erythrophyllum [50] 175 rhamnazin C. erythrophyllum [50] 176 dillenetin C. lanceolatum [52] 177 isorhamnetin C. lanceolatum [52] 178 quercetin C. leprosum, C. apiculatum [39,40,53] 179 3-0-methylquercetin C. leprosum, C. erythrophyllum [40,50] 180 quercetrin C. leprosum, C. apiculatum [39,51] 181 5,3',4'-trihydroxy-3,7-dimethoxyflavone C. leprosum [40] 182 5,3'-dihydroxy-3,7,4'-trimethoxyflavone C. leprosum [40] 183 cardamonin C. apiculatum [51] 184 pinocembrin C. apiculatum …”
Section: Triterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…During our search for bioactive natural products with tumor-selective apoptosis-inducing activity [1][2][3], we examined the MeOH extracts of medicinal plants collected in Thailand in order to find compounds that enhance DR5 promoter activity. We previously reported nine cycloartane triterpenes and six known flavonols isolated from Combretum quadrangulare (Combretaceae), with DR5 expression-enhancing activity [4]. In addition, we suggested that these compounds overcome TRAIL-resistance by upregulating DR5 expression.…”
mentioning
confidence: 94%
“…The 1 H‐NMR spectrum of 1 ( Table ) displayed two upfield doublet s resonating as an AX system at δ (H) 0.60 and 0.42 (both d , J = 4.2) assignable to cyclopropyl CH 2 H‐atoms which are characteristic of 9 β ,19‐cycloartane‐type triterpenes . It also displayed signals for three tertiary Me groups at δ (H) 1.07, 1.02, 0.94 and three secondary Me groups at δ (H) 1.00 and 1.01 (both d , J = 4.8), and 0.87 ( d , J = 6).…”
Section: Resultsmentioning
confidence: 99%